Results of the survey on the animal fauna of the Tay Con Linh mountain area, Ha Giang province - Phuong, Dang Huy; Khien, Hoang Minh; Hung, Le Manh; Truong, Nguyen Quang (Academia Journal of Biology, 2015)
The Tay Con Linh mountain area is one of the most valuable biodiversity areas of the Ha Giang province. The survey on the animal fauna of this area was carried out by the authors in 2001 and 2002. The results of the survey show that there are about 188 animal species from 70 families and 25 orders; of which, 47 mammal species are from 22 families and 8 orders, 90 aves species from 32 families and 12 orders, 51 reptilia and amphibia species from 16 families and 5 orders. 33 species of them are endangered, such as: Macaca arctoides, Hylobates concolor, Ursus malayanus, U. thibetanus, Catopuma temmincki, Neofelis nebulosa, Panthera pardus, Capricornis sumatraensis....; Psarisomus dalhousiae, Jabouilleia d¹njoui, Garrulax merulinus, Enicurus scouleri...; Palea staindachneri, Pelodiscus sinensis, Ophiophagus hannah, Physignathus cocincinus, Naja naja, Paa spinosa ... Based on these results, the recommendation is that: the local authority needs to have urgent measures for the conservation of the biological resources of this area and make a plan for the continuation of the study on the biodiversity of the Tayconlinh mountain area, in order to have scientific basis for the establishment of the Tayconlinh Nature Reserve.